State-of-the-art iron-based nanozymes for biocatalytic tumor therapy. Issue 2 (21st November 2019) - Li, Menghuan; Zhang, Hui; Hou, Yanhua; Wang, Xuan; Xue, Chencheng; Li, Wei; Cai, Kaiyong; Zhao, Yanli; Luo, Zhong
Abstract : Iron-based artificial enzyme nanomimics show promise for biocatalytic tumor therapy. Abstract : Biocatalytic tumor therapy with artificial nanoscale enzyme-mimics (nanozymes) is an emerging strategy for the therapeutic intervention of a variety of malignant conditions, which can provide the combined benefits of enzyme-dependent biocatalytic activities and nanotechnology. Generally, these novel nanocatalysts employ particular multivalent ions as the catalytic center; they have demonstrated high catalytic efficiencies, due to which they are even more potent than natural enzymes, and they also exhibit better in vivo stability, functional versatility and lower manufacturing cost. It is well established that a malignant tumor has many enzymatic mutations, which provides ample opportunities for the development of biocatalytic tumor therapy with nanozymes. Most of the current research in this area revolves around iron-based nanostructures due to their easy manufacturing process, intrinsic biocompatibility, promising physical properties, and versatile and efficient catalytic activity. A great variety of studies in the recent decade have consistently demonstrated the translational potential of iron-based nanozymes for tumor therapy. Therefore, it would be of great practical significance to summarize the previous reports on the treatment-facilitative effects and tumor cell-damaging mechanisms of iron-based nanozymes, which primarily include tumor hypoxia amelioration, Fenton-enhanced ROS damage and the activation of the ferroptosis pathway. Additionally, we also discuss the critical issues that may affect their clinical translation and future development. We hope that these iron-based nanozymes can overcome the limitations of conventional therapies and open new avenues for tumor treatment.